Climate Change and the Spread of Pathogens: Implications for Public Health - Nikhat Darakshan (International Journal of Pathogens, 2025)
Climate change plays a significant role in the spread of infectious diseases by shifting how pathogens behave, affecting how vulnerable hosts are, and changing the way diseases are transmitted.Rising global temperatures, changing precipitation levels, and extreme weather events are accelerating the spread of bacteria, viruses, fungi, and parasites, increasing the risk of outbreaks worldwide. Warmer conditions favor the survival and expansion of vector-borne diseases such as malaria, dengue, and Zika virus, while altered rainfall patterns contribute to the spread of waterborne pathogens like cholera and cryptosporidiosis. Extreme weather events, including hurricanes and floods, further exacerbate disease outbreaks by damaging sanitation infrastructure and displacing populations.The public health impact of climate-driven disease spread is profound, placing significant strain on healthcare systems and disproportionately affecting vulnerable populations, including children, the elderly, and those in low-income regions. Socioeconomic disparities and inadequate healthcare infrastructure amplify these risks, making disease mitigation efforts critical. To better prepare for and respond to the health risks posed by climate change, we must strengthen disease monitoring, invest in healthcare systems that can withstand climate impacts, and establish early warning mechanisms. Equally important is the need to cut greenhouse gas emissions, adopt sustainable environmental practices, and incorporate climate factors into public health policies. This discussion highlights the urgent need for global collaboration, interdisciplinary research, and proactive policymaking to tackle the intricate link between climate change and infectious diseases. By making public health systems more climate-resilient, we can help communities anticipate and manage climate- related health challenges, ultimately working toward a safer and healthier future for everyone.
Keywords: Climate change; Disease mitigation; infectious diseases; public health; vector-borne diseases